IMPLEMENTASI ALGORITMA BLOWFISH PADA SISTEM MANAJEMEN SURAT DENGAN PENDEKATAN RATIONAL UNIFIED PROCESS YANG RAMAH LINGKUNGAN - Filan Firmansyah; Saputra Dwi Nurchaya; Zuhana Realita Alfy (Jurnal Sistem Informasi, 2024)
In many organizations, including the Institut Teknologi Perusahaan Listrik Negara (ITPLN), letter management and organization is very important. This process is often resource-intensive and time-consuming. With the advancement of information technology, a secure digital system can help optimize letter management. The implementation of Blowfish cryptographic algorithm for encryption of important data on letter stored in a digital-based letter management system is the subject of this research. This method lowers the potential for eavesdropping and data theft. In the development process of this system, the Rational Unified Process (RUP) methodology takes the principle of green computing, which helps improve the efficiency of environmental destruction. The system adopts a paperless office paradigm, addresses the issue of operational inefficiencies, and safeguards sensitive data. The Blowfish algorithm prevents irresponsible people from compromising the database. This research produces a secure letter management information system using blowfish algorithm and developed using RUP that is environmentally friendly in contribution to the efficiency of environmental destruction caused by software development. Keywords: Blowfish Algorithm, Rational Unified Process, Data Security, Letter Management, Eco-Friendly Software